Cilia - Beals, Philip L.; Jackson, Peter; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Cilia is an open access peer-reviewed journal that publishes high quality basic and translational research on the biology of cilia and diseases associated with ciliary dysfunction. Research approaches include cell and developmental biology, use of model organisms, and human and molecular genetics. Research areas of interest include, but are not limited to: Signalling and developmental pathways involving cilia Sensory neuroscience or neurology related to cilia Diseases linked to ciliary dysfunction, including developmental defects, retinal degeneration, polycystic kidney disease Cell cycle biology related to cilia Therapeutic studies, including the use of gene therapy Cilia ultrastructure Cilia links to cell trafficking Cilia links to cytoskeletal structure and function.
Keywords: Human genetics; Molecular biology; Biochemistry; Proteins; Cell biology; Developmental biology; Cell Biology; Developmental Biology; Human Genetics; Molecular Medicine; Biochemistry, general; Receptors